IAB-BAMF-SOEP-Befragung von Geflüchteten 2016: Studiendesign, Feldergebnisse sowie Analysen zu schulischer wie beruflicher Qualifikation, Sprachkenntnissen sowie kognitiven Potenzialen - Herbert Brücker; Nina Rother; Jürgen Schupp (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2017)
Die Befragung Die IAB-BAMF-SOEP-Befragung von Geflüchteten ist eine jährliche Wiederholungsbefragung, die erstmals im Jahr 2016 4.816 erwachsene Personen in 3.554 Haushalten interviewte sowie Basisangaben von in diesen Haushalten lebenden 5.717 Minderjährigen erhoben hat. Die Studie ist als Längsschnitt konzipiert, im Jahr 2017 erfolgt die zweite Erhebungswelle derselben Haushalte und Personen. Befragt werden Geflüchtete, die vom 1. Januar 2013 bis zum 31. Januar 2016 in Deutschland eingereist sind und einen Asylantrag gestellt haben, sowie ihre Haushaltsmitglieder. Die Ziehung der Zufallsstichprobe Geflüchteter erfolgte auf Basis des Ausländerzentralregisters (AZR). Hier konnten im Zeitraum von Juni bis Dezember 2016 für 50,1 % aller im Feld bearbeiteten Adressen ein erfolgreiches Interview realisiert werden. Die Ergebnisse der Studie erlauben nach entsprechender Gewichtung verallgemeinernde Aussagen über Geflüchtete, die zwischen dem 1. Januar 2013 bis 31. Januar 2016 nach Deutschland eingereist sind. Die Daten werden ab November 2017 in anonymisierter Form der interessierten (inter-) nationalen Forschungsgemeinschaft für Sekundäranalysen zur Verfügung gestellt. – – With a representative and anonymous survey of more than 4.500 refugees, the Institute for Employment Research (IAB), the Socio-economic Panel (SOEP) at the German Institute for Economic Research (DIW Berlin) and the Research Centre on Migration, Integration and Asylum of the Federal Office for Migration and Refugees (BAMF-FZ) provide a unique and extensive dataset for analysis of forced migration and the integration of refugees. Among others the refugees were asked about their education, vocational training and work experience in home and transition countries, about the reasons they left their home countries and their experiences during their escape. Furthermore, there have been questions about their attitudes, values and expectations regarding living in Germany as well as first experiences in Germany and about their social and labor market integration. Due to the nature of sampling and by defining sample weights, the presented results are representative for the population of refugees coming to Germany from January 2013 to January 2016. After the first part of the survey was presented in November 2016 on the basis of about half of all interviews (Brücker et al., 2016), the following report provides a complete methodical documentation of the study as well as information on the field results of the entire 2016 survey year. Overall, around 64 percent of refugees received a school degree and 20 percent a vocational or university degree. Classifying their foreign educational qualification into the International Standard Classification of Education (ISCED), the results show that the average educational level of about 56 percent of the refugees is comparatively low (ISCED 0, 1 or 2), about 30 percent of the interviewees have medium level of education (ISCED 3 or 4) and about 13 percent of the refugees have a higher educational level (ISCED 6, 7 or 8). Concerning language skills, there seem to exist a diversity of mother tongues. As expected, among the interviewed refugees, the Arabic language dominates with a total of 44 percent of all native speakers, but a large number of other mother-tongues are also mentioned. Around 23 percent of the refugees report (very) good English language skills. However, more than half of the refugees report bad or even no English skills at all. In addition to the mother tongue or national language, as well as English skills, around 40 percent of respondents state that they have knowledge of at least one other language. On average, around 20 percent of refugees report good or very good German skills whereas only 45 percent state bad or no German skills at all. At the time of interviewing, the German language competences vary considerably, among others, by sex, length of stay, asylum status and level of education. Gender differences also appear in terms of educational participation and language programs in Germany. At course, offered by the BAMF, or currently attend this course. This share, however, is not evenly distributed among men and women: around 31 percent of women and around 42 of men participate in a BAMF integration course. Taking into account the family situation and, in particular, childcare, one can explain a large part of the gender differences. Concerning recognition of professional qualification, so far only one third of refugees with professional qualification applied for it. The shares vary greatly with regard to the length of stay. Thus, 25 percent of refugees who spent a maximum of one year in Germany, already applied for recognition, while 36 percent of those who are already two to a maximum of three years in Germany applied for recognition. The survey also shows that two-thirds of those who applied for recognition received help. Besides the question of the level of education and vocational education, a standardized short-term test was used in the survey, not least to identify the potential for skills and competences. More than three-quarters of the respondents participated in the cognitive test, however, the participation in the test varies with the level of education. Refugees with no, less or unknown education (ISCED 0, 1, 2 or unknown) tend to participate less than refugees with higher educational qualifications (ISCED 4 and above). The regression analysis also shows, that the test scores significantly depend on central sociodemographic characteristics such as, e.g., the age of the respondents.
Keywords: 330